Comparison of the environmental and structural performance of solid and glued laminated timber products based on EPDs. (August 2020) - Dias, A.M.A.; Dias, A.M.P.G.; Silvestre, J.D.; Brito, J. de
Highlights: A review of European solid wood and glulam EPDs was made with NativeLCA method. The European Reference Values of solid wood and glulam EPDs were determined. EPDs reviewed have insufficient information about products' mechanical behaviour. The visual strength grading method are used to estimate the EPDs strength classes. Abstract: Environmental Product Declarations (EPDs) provide quantified information based on the Life Cycle Assessment (LCA) method, and other relevant information, related to the environmental aspects of products and services. The main advantage of EPDs is the possibility of comparison of the environmental performance of various products. The balanced comparison of the environmental performance of structural products requires that their structural performance is also taken into account. This study reviews 23 EPDs of solid wood (SW) and glued laminated timber (GLT) structural elements developed according to the EN 15804 product category rules. The NativeLCA methodology is applied in this study to review LCA procedures and technical data of EPDs, as well as to determine and compare the European Reference Values (ReVa) for the environmental impacts of SW and GLT products. Since the strength classes are not indicated in the documents, a methodology to estimate them and compare the environmental impacts of SW and GLT products was developed. The methodology proposed is applied to the selected EPDs to calculate and compare the ReVa of each estimated strength class. The environmental impacts' comparison of various strength classes ReVas' are also made considering a structurally equivalent functional unit. The methodology to obtain the SW's strength classes from EPDs is based on the species of wood, country of origin and mean density, while for GLT strength classes are inferred from the type of GLT (homogenous or combined) and mean density. The calculation of ReVa for each SW and GL's strength class allows the comparison of the environmental impacts of products with different structural performances. The majority of SW and GLT EPDs have been identified as C24 and GL24h strength classes, respectively. For the same structural equivalent functional unit, and for GWP, EP and PE-NRe environmental impact categories, the SW products presented lower environmental impacts than the GLT ones. An increase of GLT's strength classes decreases PE-Re and PE-NRe and increases GWP environmental impacts for the functional unit considered.